Circulating androgens and postmenopausal ovarian cancer risk in the Women's Health Initiative Observational Study. Issue 8 (15th February 2019) - Trabert, Britton; Michels, Kara A.; Anderson, Garnet L.; Brinton, Louise A.; Falk, Roni T.; Geczik, Ashley M.; Harris, Holly R.; Pan, Kathy; Pfeiffer, Ruth M.; Qi, Lihong; Rohan, Thomas; Wentzensen, Nicolas; et al.
Abstract : Our knowledge of epidemiologic risk factors for ovarian cancer supports a role for androgens in the pathogenesis of this disease; however, few studies have examined associations between circulating androgens and ovarian cancer risk. Using highly sensitive LC–MS/MS assays, we evaluated associations between pre‐diagnostic serum levels of 12 androgens, including novel androgen metabolites that reflect androgen activity in tissues, and ovarian cancer risk among postmenopausal women in a nested case–control study in the Women's Health Initiative (WHI) Observational Study (OS). We frequency‐matched 169 ovarian cancer cases to 410 controls from women enrolled in WHI‐OS who were not using menopausal hormones at enrollment/blood draw. We estimated associations overall and by subtype (n = 102 serous/67 non‐serous) using multivariable adjusted logistic regression. Androgen/androgen metabolite levels were not associated with overall ovarian cancer risk. In analyses by subtype, women with increased levels of androsterone‐glucuronide (ADT‐G) and total 5‐α reduced glucuronide metabolites (markers of tissue‐level androgenic activity) were at increased risk of developing non‐serous ovarian cancer: ADT‐G tertile (T)3 versus T1 odds ratio [OR] (95% confidence interval [CI]) 4.36 (1.68–11.32), p ‐heterogeneity 0.002; total glucuronide metabolites 3.63 (1.47–8.95), 0.002. Risk of developing serous tumors was unrelated to these markers. ADT‐G and total glucuronide metabolites, better markers of tissue‐level androgenic activity in women than testosterone, were associated with an increased risk of developing non‐serous ovarian cancer. Our work demonstrates that sex steroid metabolism is important in the etiology of non‐serous ovarian cancers and supports a heterogeneous hormonal etiology across histologic subtypes of ovarian cancer. What's new?: Sex steroids play a role in ovarian carcinogenesis but associations between circulating androgen levels and ovarian cancer risk are inconsistent. Using mass spectrometry, the authors focused on 5α‐reduced androgen metabolites that cannot be metabolized into estrogen and therefore better reflect androgenic activity in tissues. They found androsterone‐glucuronide levels associated with increased risk of non‐serous tumors, the less frequent cancer form, pointing to unique subtype‐specific influences of androgens in ovarian malignancies.